Giant Cell Arteritis Presenting with Mania, Psychosis, and Cognitive Dysfunction: A Case Report - Latvala, Heidi Madeleine; Reitan, Solveig Klæbo; Vaaler, Arne Einar (Case Reports in Psychiatry, 2023)
Background. Giant cell arteritis (GCA) is an autoimmune vasculitis affecting medium- and large-sized arteries. Vascular inflammation may lead to narrowing of the arterial lumen, and acute occlusion may result in vision loss and stroke. The classical symptoms include headache, fever, and jaw claudication. However, there is an increasing recognition of atypical presentations. Case Presentation. We report a case of a 70-year-old woman presenting with fluctuating manic symptoms and confusion, in addition to headache and musculoskeletal pain. After diagnosis of GCA, treatment with corticosteroids gradually improved the somatic symptoms. Conclusion. Corticosteroids led to a temporary exacerbation of manic symptoms, which improved after 3 to 4 weeks of continuous treatment, indicating that the symptoms were most likely associated with GCA. The patient manifested with clinical features and a clinical course that has, to our knowledge, not been described or published before. Therefore, GCA may be an underdiagnosed disease in psychiatric populations and should be considered in case of atypical, new-onset psychiatric disorders in the elderly.